People and places: A 2001 census atlas of the UK - Dorling, D; Thomas, B (Policy Press, 2004)
People and places: A 2001 Census atlas of the UK provides an at-a-glance guide to social change in the UK at the start of the new millennium. It is the first comprehensive analysis of the 2001 Census and offers unique comparisons with the findings of the previous Census a decade ago. Over 500 full-colour maps covering 125 topics clearly illustrate the state of UK society today and how it is changing. The trends are explained and elaborated upon in the accompanying text. Using population maps in addition to conventional maps, the atlas covers all the major census topics at local authority level. Key features include an illuminating graphic summary of over 100,000 key demographic statistics; new cartographic projections and techniques used throughout ; appendix incorporating rankings for 25 selected topics by local authority; comparison with the 1991 census to identify national and local trends and up-to-date analysis and discussion of the implications of current trends for future policy. This authoritative atlas is essential reading for those interested in the current social geography of the UK, how it has changed and how it appears to be changing, including for planners in local authorities, health authorities and a wide range of statutory and voluntary organisations. It is also an invaluable resource for policy makers, journalists, politicians, students and academics interested in human geography and social change.